Reasons for the removal and transfer of the parish priest - Leszczyński, Grzegorz (Prawo Kanoniczne, 2023)
The article is an answer to the question: whether the bishop of a diocese has the right to remove a parish priest always or, while maintaining the procedures, he can do it only in certain circumstances. It should be stated that there is no voluntary removal or transfer of a parish priest. Each bishop of a diocese is bound not only by the procedure, but above all by the reasons, which are precisely defined in the Code of Canon Law. Therefore, an action that is inconsistent with the procedure, but also for reasons other than those specified in the Code, may constitute an abuse of power, and therefore a crime.